2018
DOI: 10.1002/cssc.201801767
|View full text |Cite
|
Sign up to set email alerts
|

Excellent Compatibility of the Gravimetric and Areal Capacitances of an Electric‐Double‐Layer Capacitor Configured with S‐Doped Activated Carbon

Abstract: Coffee grounds were converted into S-doped activated carbon (SAC) in the presence of an active agent and S dopant through a one-step synthesis approach. Carbonization, activation, and S doping was achieved through this one-step methodology. The SAC was used as an electrode material for the preparation of a symmetric electrical-double-layer capacitor (EDLC), and the influence of the loading mass of the active materials on the capacitive behaviors was investigated. The assembled SAC-based symmetric EDLC not only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…16,17 Recent supercapacitor studies of activated carbon electrode can be found elsewhere. 15,[18][19][20]…”
Section: Activated Carbon (Ac)mentioning
confidence: 99%
“…16,17 Recent supercapacitor studies of activated carbon electrode can be found elsewhere. 15,[18][19][20]…”
Section: Activated Carbon (Ac)mentioning
confidence: 99%
“…In order to prevent low charge storage, the best match between the size of the electrolyte ion and the pores needs to be found. Recent supercapacitor studies can be performed elsewhere on activated carbon electrodes [66]. Another type is pseudo-capacitors, which help in redox processes or the transport of charge between electrolytes and electrodes.…”
Section: Types and Classification Of Supercapacitorsmentioning
confidence: 99%
“…al. [117] prepared S-doped AC by calcination of the mixture of coffee grounds, KOH, and MgSO 4 at 4 : 4 : 1 mass ratio at 800 °C for 1 h in the furnace under argon atmosphere (Figure 8). In this one-pot synthesis methodology, coffee grounds, KOH, and MgSO 4 acted as carbon source, activating agent, and sulfur source, respectively.…”
Section: Biomass-assisted Synthesismentioning
confidence: 99%
“…Ma et. al [117] . prepared S‐doped AC by calcination of the mixture of coffee grounds, KOH, and MgSO 4 at 4 : 4 : 1 mass ratio at 800 °C for 1 h in the furnace under argon atmosphere (Figure 8).…”
Section: Synthesis Strategy Of S‐doped Carbon As Electrode Materials For Sc Applicationsmentioning
confidence: 99%